Association of Zinc and Vitamin A with Pulmonary TB Infection and PTB-HIV CO-Infection - Salma Mumtaz, Khalida Shaikh, Rozina Mangi, Abdul Ghafoor, Fahima Rani, Aqsa Naeem (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives of Study: To assess serum zinc and vitamin A levels among patients of PTB and PTB-HIV co-infection. Study Setting: Physiology department, Chest Medicine department, HIV center and Medical Research Centre, LUMHS Jamshoro and the Institute of Chest Diseases in Kotri TB Sanatorium Hospital. Material and Methods: In this cross-sectional comparative study, patients having PTB and PTB-HIV co-infection were recruited from Chest Medicine Department and the Institute of Chest Diseases in Kotri after approval from Ethical Review Committee, LUMHS, Jamshoro. Study participants divided in two groups; one group (n=114) included diagnosed cases of PTB having no co-infection while in other group (n=9) there were patients having coinfection of PTB and HIV. The sampling method was non probability purposive. Blood samples were obtained intravenously after informed consent. Serum zinc levels were determined by zinc ELIA kit and vitamin A by vitamin A ELISA kit. Results: Mean age of study participants was 28.88 years and among them 69.11 percent were AFB positive. To find out drug resistance, gene Xpert was done that was positive in 95.93 percent of patients. Vitamin A and zinc levels were decreased in the main but furthermore they were compared between PTB and PTB-HIV coinfection. Mean of vitamin A in PTB and PTB/HIV co-infection groups were 0.07 and 0.02 respectively, (p-value=0.03 and t value=2.09) that show statistically significant difference in vitamin A levels in two groups. Mean of serum zinc in PTB and PTB/HIV co-infection groups were 2.84 and 1.14 respectively, (p-value<0.01 and t value=2.89) that show highly significant difference statistically. Conclusion: Vitamin A and zinc are significantly less in coinfected people.